Counting Conditions on Newborn Bloodspot Screening Panels in Australia and New Zealand - Natasha Heather; Ronda F. Greaves; Kaustuv Bhattacharya; Lawrence Greed; James Pitt; Carol Wai-Kwan Siu; Mark de Hora; Ricky Price; Enzo Ranieri; Tiffany Wotton; Dianne Webster (MDPI AG, 2024)
A greater number of screened conditions is often considered to equate to better screening, whereas it may be due to conditions being counted differently. This manuscript describes a harmonised Australasian approach to listing target conditions found on bloodspot screening panels. Operational definitions for target disorders and incidental findings were developed and applied to disorder lists. A gap analysis was performed between five, state-based Australian newborn screening programme disorder lists and the single national New Zealand and state-level Californian versions. Screening panels were found to be broadly similar. Gap analysis with Californian data reflected differences in jurisdictional approval (for example, haemoglobinopathies and lysosomal disorders not being recommended in Australasia). Differences amongst Australasian panels reflected varied the timeframes recommended in order to implement newly approved disorders, as well as decisions to remove previously screened disorders. A harmonised approach to disorder counting is essential to performing valid comparisons of newborn bloodspot screening panels.